THE PERCENTAGE OF OXYGEN ABSORPTION BY VANNAMEI SHRIMP (LITOPENAEUS VANNAMEI) WHICH IS SUPPORTED BY THE PADDLEWHEEL - Ade Kurniawan (Universitas Tidar, 2021)
A dynamic model was used to obtain optimal value or amount in the application of paddlewheel. Stella 9.1.4 software programing was employed to find relationships among parameters. The aims of this reasearch was to determine the percentage of oxygen uptake by vannamei shrimp (Litopenaeus vannamei) which is supported by 1 paddlewheel. The result showed that the optimal number of paddlewheel was 1 paddlewheel with Standart Aeration Efficiency was 1,31 kgO2/kWh. The percentage of oxygen absorption on vannamei shrimp until final cultivation was 24% during the cultivation, the percentage of oxygen absorption on vannamei shrimp had increased. In this research, total oxygen demand was 567 ppm, shrimp production was 1054,88 kg, the amount of feed was 2278,1 kg with a pond area was 600 m2, stocking density was 133 PL/m2 during a cultivation period of 98 days.Keyword : Paddlewheel, Oxygen, Vannamei shrimp (Litopenaeus vannamei)